2020
DOI: 10.3390/jcm9103133
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Periprosthetic Infection in Patients with Tumor Prostheses Following Resection for Musculoskeletal Tumor of the Lower Limb

Abstract: Tumor prostheses for the lower limb following resection of musculoskeletal tumors is useful limb salvage management; however, as compared with routine total joint replacement, an increased incidence of deep periprosthetic infection of tumor prosthesis has been observed. The risk factors for periprosthetic infection of tumor prosthesis remain unclear. This study examines the risk factors and outcomes of periprosthetic infection. This was a retrospective observational study including 121 patients (67 males and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 41 publications
(68 reference statements)
2
25
0
2
Order By: Relevance
“…We found no difference in the risk of deep infection between the two cohorts. Our findings (11%, 8 out of 72) are comparable to Fujiwara et al 42 who in a retrospective study evaluated tumor-prostheses in the lower extremities and demonstrated a rate of 12% in 121 both fixed- and rotating-hinge tumor-prostheses. Proximal tibia is the predominant location for deep infection, and hence also the most common place for amputations caused by deep infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found no difference in the risk of deep infection between the two cohorts. Our findings (11%, 8 out of 72) are comparable to Fujiwara et al 42 who in a retrospective study evaluated tumor-prostheses in the lower extremities and demonstrated a rate of 12% in 121 both fixed- and rotating-hinge tumor-prostheses. Proximal tibia is the predominant location for deep infection, and hence also the most common place for amputations caused by deep infection.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggest the use of silver-coated implants. 40 , 42 , 46 , 47 Streitbuerger et al 47 demonstrated promising results when comparing silver-coated implants with standard implants and Pala et al 40 advocate using silver- and iodine-coated implants in high-risk patients to reduce re-infection rate. However, none of the studies demonstrated statistical difference when comparing silver-coated and standard implants.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons behind the high risk of complications leading to reoperations associated with mega prosthesis surgery are not completely determined. One can assume that large wound exposures and resections of the surrounding soft tissue, prolonged surgical time and the fact that the patients often are treated with chemotherapy and/or radiotherapy in near proximity to the operation might increase the risks [ 17 ]. Since the multivariate regression analysis in the current study showed no other significant risk factor for infection than sarcoma, it is difficult to predict the outcome or risk for complications for a certain patient.…”
Section: Discussionmentioning
confidence: 99%
“…High infection rate after surgery with mega prostheses has been described in several earlier studies. Bus et al, Capanna et al, Morii et al and Fujiwara et al showed infection rates of 12–17% [ 6 , 17 19 ]. It is hard to explain why the infection rate in the current study is slightly higher than in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This offers clinicians an opportunity to modify perioperative conditions in order to prevent PJI. Fujiwara et al analysed the data of 121 patients undergoing the resection of musculoskeletal tumour of the lower limb conjoined with the implantation of tumour prosthesis [8]. This subgroup of patients is more prone to the development of PJI than patients without a local tumour at the time of TJA and there is a growing effort to stratify tumour patients individually according to additional risk factors.…”
mentioning
confidence: 99%